1984
DOI: 10.1159/000149553
|View full text |Cite
|
Sign up to set email alerts
|

Aleutian Disease Virus in B and T Lymphocytes from Blood and Spleen and in Bone Marrow Cells from Naturally Infected Mink

Abstract: In the nuclei of 4% of peripheral blood or spleen mononuclear cells (MNC), Aleutian disease virus (ADV)-specific antigens were found by a direct immunofluorescence test. The MNC were further fractionated by nylon wool, affinity chromatography using Staphylococcus aureus protein, or Percoll gradient techniques. ADV and specific antigens were detected in MNC fractions enriched in either the B or T lymphocytes. In the bone marrow, up to 40% antigen-positive cells were demonstrated over a period of 15 months. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
3
20
0
Order By: Relevance
“…Of particular interest is the so far undescribed existence of replicative ADV DNA forms in bone marrow cells. These findings supplement the detection of ADV-specific antigen and infectious virus in bone marrow cells of naturally infected mink (Roth et al, 1984). It is tempting to speculate that this site is of importance for the persistent course of the disease, e.g.…”
supporting
confidence: 62%
“…Of particular interest is the so far undescribed existence of replicative ADV DNA forms in bone marrow cells. These findings supplement the detection of ADV-specific antigen and infectious virus in bone marrow cells of naturally infected mink (Roth et al, 1984). It is tempting to speculate that this site is of importance for the persistent course of the disease, e.g.…”
supporting
confidence: 62%
“…ADV-SL3 exhibits a strong lymphotropism in vivo and in vitro. ADV-specific antigen has been detected in mononuclear cells isolated from naturally infected mink (Roth et al, 1984) and virus replication can be demonstrated in vitro by infecting enriched T and B lymphocytes derived from ADV-negative mink .…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we report on the RF DNA of the ADV isolate SL3 (van Dawen et al, 1983), which shows a marked lymphotropism in vivo and in vitro (Roth et al, 1984;Kaaden et al, 1986). The virus genome was physically mapped and the monomer RF DNA characterized with emphasis on its terminal structures.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, it was suggested that ADV persisted and replicated in the M~b (Porter et al, 1969); however, this has not been substantiated (Roth et al, 1984) and therefore the virus-producing target cell(s) remains unknown. Recent findings suggest a new and rather different role of the M~b in the pathogenesis of AD.…”
Section: Role Of the Macrophage In Virus Persistencementioning
confidence: 99%